Early endosomal maturation of MHC class II molecules independently of cysteine proteases and H-2DM - Villadangos, José A. (Oxford University Press, 2000)
Major histocompatibility complex (MHC) class II molecules bind and present to CD4(+) T cells peptides derived from endocytosed antigens. Class II molecules associate in the endoplasmic reticulum with invariant chain (Ii), which (i) mediates the delivery of the class II–Ii complexes into the endocytic compartments where the antigenic peptides are generated; and (ii) blocks the peptide-binding site of the class II molecules until they reach their destination. Once there, Ii must be removed to allow peptide binding. The bulk of Ii–class II complexes reach late endocytic compartments where Ii is eliminated in a reaction in which the cysteine protease cathepsin S and the accessory molecule H–2DM play an essential role. Here, we here show that Ii is also eliminated in early endosomal compartments without the intervention of cysteine proteases or H–2DM. The Ii-free class II molecules generated by this alternative mechanism first bind high molecular weight polypeptides and then mature into peptide-loaded complexes.